Parallel AAA and mobile IP registrarion for high performance and scalable mobile roaming - Demirkol, Aykut Soner. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
An important part of the communication technology currently depends on the wireless networking. With the increase in the connectivity needs, many types of wireless technologies have been deployed to ensure the coverage of the living areas using short and long range networks. Due to the access needs for efficient and continuous connectivity, interoperability became a very important issue. Mobile IPv4 is a well accepted protocol, standardized by IETF for such needs. Mobile IPv4 enables a wireless node to move from one infrastructure to another without disrupting the end-to-end TCP communication. Almost all IP based wireless technologies that are already developed or under development aim Mobile IP support. Support for Authentication, Authorization and Accounting (AAA) architectures are also included in latter Mobile IP standards. IETF draft standard “RADIUS Mobile IPv4 extensions” defines new attributes and methods to provide AAA support for Mobile IPv4. This standard defines new interactions before starting the Mobile IP registration between a mobile node and RADIUS servers. The preliminary RADIUS server interactions increase the overall time needed for Mobile IP with RADIUS registration significantly. In this thesis work, a new solution, named “Parallel AAA and Mobile IP Registration” is proposed to decrease the communication overhead associated with preliminary RADIUS server interactions. In the proposed solution, the existence of preestablished Foreign Agent - Home Agent security associations are assumed. A simulation model of the proposed solution and the RADIUS Mobile IPv4 extension standard is developed to compare their overall registration time performance. The simulation model also provides a scalability analysis of overall registration time. It is also shown that the proposed solution performs better under various communications link and server hardware settings.
Keywords: Mobile communication systems.; Computer network protocols.